The Effect of Planting Media on Several Chemical Properties of Soil and Growth of Moringa Stem Cuttings (Moringa oleifera Lam.) - Wahdah, Rabiatul (JOURNAL OF TROPICAL SOILS, 2025)
This research was conducted to determine the effect of planting media on the growth of Moringa stem cuttings and determine the best planting media for growing Moringa stem cuttings. The research was carried out in July-October 2023. Located on the Wasaka III Student Dormitory grounds, Lambung Mangkurat University, Banjarbaru, South Kalimantan Province. The research was carried out using a one-factor Completely Randomized Design (CRD) method with four treatments and five replications to obtain 20 experimental units. The treatments given were as follows: m0 (Control): 6 kg peat soil, m1: 5 kg peat soil + 1 kg husk charcoal, m2: 5 kg peat soil + 1 kg laying hen manure, m3: 5 kg peat soil + 0.5 kg husk charcoal + 0.5 kg laying hen manure. The results showed that the planting medium had a significant effect on soil pH, shoot length, number of leaf stalks, root length and root volume of Moringa stem cuttings. However, it had no real effect on the number of shoots on Moringa stem cuttings. Based on research that has been carried out, it shows that planting media given husk charcoal and manure increases the available P content by 241.34 ppm, N-dd 1.70 me/100 g, and K-dd 1.65 me/100 g in the soil. peat and can increase the pH of peat soil from acid to neutral. The treatment also had a very significant effect on the growth of shoot length, number of leaf stalks, root length and root volume of Moringa stem cuttings. It can be suggested that the best planting medium for the growth of Moringa plants is to provide 0.5 kg of husk charcoal + 0.5 kg of laying hen manure on peat soil.